Frontline . Frontline - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. "Back in the USSR": An American family returns to the USSR after 20 years to see what has changed during the perestroika period. Contributors: Woodruff, Judy (Anchor) История американской семьи, которая 20 лет назад жила в СССР и возвратилась туда, чтобы посмотреть, что изменилось за время перестройки. Создатели: Вудруф, Джуди (Ведущий/Ведущая)